استخدام نموذج الانحدار الخطي المعمم (GLM) لتسعير التأمين الطبي - زكي، نيفين محسن أحمد; جمال عبد الباقي واصف; البلقيني، محمد توفيق إسماعيل (المجلة العلمية للدراسات والبحوث المالية والتجارية: علمية محكمة., 2024)
The problem of determining the price in any branch of insurance is a complex process, because insurance prices are not subject to the laws of demand and supply that control the prices of goods and services, but rather deal with future possibilities related to the frequency of accidents and the size of the expected loss. on the other hand, setting insurance prices in an exaggerated way weakens the competitive position of the insurance companies, and setting insurance prices at a low-level lead to insufficient income to cover the expenses incurred in carrying out its operations, and in both of the previous cases, it will affect the company’s ability to continue. in its business successfully. from here, this study sought to search for methods that can be used to price medical insurance in Egypt. for this purpose, the study used generalized linear regression models. these methods were applied to some insurance companies operating in medical insurance in Egypt during the period from 2012 to 2020. the study concluded that the most important variables affecting the pricing of medical insurance in Egypt are compensation, commission rate, and production costs, and that the best method for pricing medical insurance is in Egypt, under generalized linear regression models, it is the log normal method. تعتبر مشكلة تحديد السعر في أي فرع من فروع التأمين عملية معقدة، وذلك نظرا لأن أسعار التامين لا تخضع لقوانين الطلب والعرض التي تتحكم في أسعار السلع والخدمات، وإنما تتعامل مع احتمالات مستقبلية تتعلق بمعدل تكرار وقوع الحوادث، وحجم الخسارة المتوقعة. ومن ناحية أخرى فإن تحديد أسعار التأمين بشكل مبالغ فيه يضعف من المركز التنافسي لشركات التأمين، كما أن تحديد أسعار التأمين بأقل مما يجب يؤدي إلى عدم كفاية الدخل الذي تحصل عليه لتغطية النفقات المترتبة على مزاولة عملياتها، وفي كلتا الحالتين السابقتين سوف يؤثر على قدرة الشركة على الاستمرار في أعمالها بنجاح. من هنا سعت هذه الدراسة إلى البحث عن الأساليب التي يمكن استخدامها لتسعير التأمين الطبي في مصر. واستخدمت الدراسة لهذا الغرض نماذج الانحدار الخطي المعممة. وتم تطبيق تلك الأساليب على بعض شركات التأمين العاملة في التأمين الطبي في مصر خلال الفترة من 2012 إلى 2020. وتوصلت الدراسة إلى أن أهم المتغيرات التي تؤثر في تسعير التأمين الطبي في مصر هي كل من التعويضات ومعدل العمولات وتكاليف الإنتاج وأن أفضل طريقة لتسعير التأمين الطبي في مصر في ظل نماذج الانحدار الخطي المعمم هي طريقة Log Normal.